Sustainable political commitment is necessary for institutionalizing community participation in health policy-making: Insights from Iran - Maryam Rahbari Bonab; Fatemh Rajabi; Abouali Vedadhir; Reza Majdzadeh (BMC, 2024)
Abstract Background Community participation is currently utilized as a national strategy to promote public health and mitigate health inequalities across the world. While community participation is acknowledged as a civic right in the Constitution of Iran and other related upstream documents, the government has typically failed in translating, integrating and implementing community participation in health system policy. The present study was conducted to determine the level of public voice consideration within the health policy in Iran and address fundamental interventions required to promote the public voice in the context of Islamic Republic of Iran (IRI). This study has originality because there is no study that addresses the requirements of institutionalizing community participation especially in low-middle-income countries, so Iran's experience can be useful for other countries. Methods Methodologically, this study utilized a multi-method and multi-strand sequential research design, including qualitative, comparative and documentary studies. In the first phase, the current level of community participation in the health policy cycle of Iran was identified using the International Association for Public Participation (IAP2) spectrum. In the second phase, a comparative study was designed to identify relevant interventions to promote the community participation level in the selected countries under study. In the third phase, a qualitative study was conducted to address the barriers, facilitators and strategies for improving the level of public participation. Accordingly, appropriate interventions and policy options were recommended. Interventions were reviewed in a policy dialogue with policy-makers and community representatives, and their effectiveness, applicability and practical feasibility were evaluated. Results Based on the IAP2 spectrum, the level of community participation in the health policy-making process is non-participation, while empowerment is set at the highest level in the upstream documents. Moreover, capacity-building, demand, mobilization of the local population, provision of resources and setting a specific structure were found to be among the key interventions to improve the level of community participation in Iran's health sector. More importantly, "political will for action" was identified as the driving force for implementing the necessary health interventions. Conclusions To sum up, a paradigm shift in the governing social, economic and political philosophy; establishing a real-world and moral dialogue and communication between the government and the society; identifying and managing the conflicts of interest in the leading stockholders of the healthcare system; and, more importantly, maintaining a stable political will for action are integral to promote and institutionalize participatory governance in the health sector of Iran. All of the above will lead us to scheme, implement and institutionalize suitable interventions for participatory governance in health and medicine.